The impact of a self-management program on volume overload among patients with heart failure in Thailand: A quasi-experimental study - Lungkawong, Napassawan; Polsook, Rapin (Belitung Nursing Journal, 2025)
Background: Volume overload is a common and serious complication in patients with heart failure, often leading to hospital readmissions and decreased quality of life. Effective self-management strategies are essential in preventing fluid accumulation and improving patient outcomes. Mobile technology offers a scalable means to support such interventions, particularly in culturally specific contexts. Objective: This study aimed to evaluate the effectiveness of a self-management program delivered via the LINE application in reducing volume overload among Thai patients with heart failure. Methods: A quasi-experimental design was employed with 46 participants randomly assigned to either a control or experimental group. The control group received standard care, while the experimental group participated in a four-week self-management program based on Lorig and Holman’s theoretical framework, focusing on six key skills and three self-care tasks. Volume overload was assessed using a modified Framingham criteria-based instrument with confirmed content validity and acceptable reliability. Data were analyzed using paired and independent t-tests with IBM SPSS version 21. Results: Post-intervention, the experimental group showed a significant reduction in fluid volume overload scores (M = 6.96, SD = 1.46) compared to pre-intervention (M = 8.65, SD = 1.57, t = 9.90, p <0.001, Cohen’s d = 1.11). The control group showed no significant change. An independent t-test confirmed a statistically significant difference between the experimental and control groups post-intervention (t = 3.67, df = 44, p <0.001, Cohen’s d = 1.08), indicating a substantial effect of the intervention. Conclusion: The self-management program via the LINE application effectively reduced volume overload in Thai patients with heart failure. Integrating culturally familiar mobile technology and structured self-care education significantly enhanced patient engagement and health outcomes. This study highlights the importance of incorporating digital tools into patient education and follow-up for nursing practice to empower individuals in managing chronic conditions like heart failure. Future research should explore long-term impacts and scalability across diverse healthcare settings. Trial Registry Number: Thai Clinical Trials Registry (TCTR20241124001)